Cryptic evidence for the former presence of lawsonite in blueschist and eclogite. (17th November 2020) - Chapman, Timothy; Clarke, Geoffrey L.
Abstract: Cryptic geochemical indicators of prograde lawsonite breakdown are established in basic and metasedimentary Eocene blueschist and eclogite in New Caledonia utilizing phase equilibria modelling and synchrotron X‐ray fluorescence mapping. Lawsonite–epidote‐bearing eclogite has garnet with concentric zones depleted in the LREE and MREE, and clinozoisite with high‐Sr rims, which geochemically record a prograde stage of lawsonite stability. These records persist in eclogite that now lacks lawsonite, and may be used to validate texturally based interpretations for prograde lawsonite stability. The compositional trends depend on extrinsic and intrinsic variables, including bulk rock composition, which determine the rock‐forming and accessory minerals that host Sr and the REEs. Distinct prograde reaction histories are recorded by two eclogite terranes in NE New Caledonia due to subtle distinctions in their protolith whole‐rock compositions.